AutoAssemblyD software para submissão e gerenciamento de montagem de genomas a partir de modelos XML - VERAS, Adonney Allan de Oliveira (Universidade Federal do Pará, 2017)
Technologies for second-generation sequencing provided a major breakthrough of the genome, making its use a landmark that has revolutionized biology. These platforms are characterized by a reduction in sequencing time, high data production and low cost per base sequenced, however, these devices produce data mostly consist of short readings which represents a major challenge for reconstruction of the genome due to this new feature readings of computational tools had to be developed to accomplish the task of assembling their example we Velvet, AllPaths, Abyss, SOAPdenovo2, Edena. However, most of these applications are executed through command lines extended and composed of several parameters must follow the standard syntax to use, because in case of errors in the syntax is the possibility of not obtaining the best result, with the aim of solve this problem we present the AutoAssemblyD that besides providing the use of these assemblers through a graphical interface also enables the management of these executions remotely.